Attention-deficit/hyperactivity disorder traits: prevalence and differential association with internet addiction - Law Mei-Yui; Siaw Yan-Li; Chua Kah-Heng; Sathish Rao Appalanaidu (Institute of Advanced Engineering and Science, 2026)
Attention-deficit/hyperactivity disorder (ADHD) traits in adults have garnered global attention due to their detrimental effects on individuals’ daily functioning. To date, there has been a scarcity of studies conducted on adult ADHD traits in Malaysia, particularly among university students. Therefore, this study aimed to explore the prevalence of ADHD, examine the correlation and predictive relationship between ADHD and internet addiction, compare internet addiction between ADHD screen-positive and screen-negative individuals, and determine the gender differences in ADHD. This study adopted a cross-sectional quantitative design, involving 1,204 voluntarily participating respondents. Data were collected using the Internet Disorder Scale (IDS-15) and the Adult ADHD Self-Report Scale (ASRS) v1.1. The findings revealed that more than a quarter (27.80%) of participants screened positive for ADHD traits. Additionally, a significant positive correlation and predictive relationship were identified between adult ADHD traits and internet addiction. Furthermore, internet addiction levels were significantly higher among ADHD screen-positive individuals compared to ADHD screen-negative individuals. However, no significant gender differences were observed in ADHD traits. Effective interventions should be developed to mitigate the adverse effects of ADHD traits on the daily functioning of university students. Moreover, efforts to address internet addiction should consider the presence of ADHD traits in this population.